Trehalose and (iso)floridoside production under desiccation stress in red alga Porphyra umbilicalis and the genes involved in their synthesis. Issue 6 (25th August 2020) - Cao, Yuanyu; Ashline, David J.; Ficko‐Blean, Elizabeth; Klein, Anita S.
Abstract : The marine red alga Porphyra umbilicalis has high tolerance toward various abiotic stresses. In this study, the contents of floridoside, isofloridoside, and trehalose were measured using gas chromatography mass spectrometry (GC‐MS) in response to desiccation and rehydration treatments; these conditions are similar to the tidal cycles that P. umbilicalis experiences in its natural habitats. The GC‐MS analysis showed that the concentration of floridoside and isofloridoside did not change in response to desiccation as expected of compatible solutes. Genes involved in the synthesis of (iso)floridoside and trehalose were identified from the recently completed Porphyra genome, including four putative trehalose‐6‐phosphate synthase (TPS) genes, two putative trehalose‐6‐phosphate phosphatase (TPP) genes, and one putative trehalose synthase/amylase (TreS) gene. Based on the phylogenetic, conserved domain, and gene expression analyses, it is suggested that the Pum4785 and Pum5014 genes are related to floridoside and isofloridoside synthesis, respectively, and that the Pum4637 gene is probably involved in trehalose synthesis. Our study verifies the occurrences of nanomolar concentrations trehalose in P. umbilicalis for the first time and identifies additional genes possibly encoding trehalose phosphate synthases.